Study of the Biological Developmental Characteristics of the Eye in Children After Laser Surgery for the Treatment of Retinopathy of Prematurity - Zeng, Xianlu; Chen, Miaohong; Zheng, Lei; Tian, Ruyin; Chen, Yi; He, Honghui; Zeng, Jian; He, Jicang; Zhang, Guoming (Frontiers in Medicine, 2022)
OBJECTIVE: To observe the differences in ocular biology between premature infants who had undergone retinal laser photocoagulation (LP) for retinopathy of prematurity (ROP) and full-term infants and to investigate the relationships between these differences and the development of the refractive state. METHODS: This retrospective, cross-sectional study included 25 children (50 eyes) who had had received laser treatment for ROP (laser group) and 29 full-term infants (58 eyes) who had not (control group). Basic information, spherical equivalent (SE), and best corrected visual acuity (BCVA) were collected from the two groups. Ocular biology data were measured using an IOL Master 700 instrument and the data were processed using MATLAB. The data markers included CCT, anterior and posterior surface CCR, ACD, LT, lens anterior and posterior surface curvature radius and AL. RESULTS: 1. There were statistically significant differences in all observation markers between the two groups (P<0.05). 2. The CCT, ACD, and LT changed significantly with age in both groups of children (P < 0.05). The age of children in both laser and control groups was negatively correlated with SE and LogMAR (BCVA) (P< 0.05). 3. In full-term infants, during the process of emmetropization, AL growth was accompanied by anterior chamber deepening and lens thinning (P < 0.05). In the laser group, the ocular biomarkers were not significantly altered (P < 0.05). 4. Analysis of the correlations of gestational age at birth with ocular biomarkers and refractive status in children in the laser group showed a positive correlation between gestational age at birth and AL (P<0.05) but no other correlations with the other biomarkers (P>0.05). Moreover, gestational age at birth was negatively correlated with SE and LogMAR (BCVA) (P<0.05) in children in the laser group. Conclusions: 1. Compared to full-term infants, children with ROP laser surgery have a thin central corneal thickness, steep corneas, shallow anterior chambers, thicker lenses, "rounder" lens morphology, increased refractive power, and short eye axes, leading to the development of myopia. 2. The lower the gestational age at birth, the greater the likelihood of myopia in children after ROP laser treatment.